Factors influencing the natural gas price in Malaysia / Dian Shafiqa Fatanah - Fatanah, Dian Shafiqa (Faculty of Business and Management, 2010)
Natural gas is a vitally important source of energy for all sectors of the economy in Malaysia. There are several factors that influence supply and demand, such as storage of natural gas, seasonality, whether, production disruptions, and oil prices. The purpose of this study is to determine the main factor that influences the price of the natural gas in Malaysia. Furthermore, it is also conduct in order to identify the relationships between the independent variables (storage capacity, production disruptions, and oil price) and the dependent variables (natural gas price).